The Evolution of Nursing Education: Preparing Future Generations for Complex Healthcare Challenges - Dabiah Moubark Ali Al Qahtani; Manal Saeed Alaklabi; Mona Dahi Salim Alharbi; Samiah Ghudayfan Alanazi; Eman Mohammed Ali Al-Zahrani; Rawan Dafer Ali AlAmri; Lulu Hussain Alkhurissi; Ashwaq Hajji Alanazi; Asma Khalaf Almutairi; Aeshah Thaar Samer Almutairi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Historically, the requirements for the nursing profession changed throughout the twentieth and twenty-first centuries. This incorporates improved anesthetic care, based on knowledge, upgraded medical technology and the shift of concentration towards the patient, interaction with other professionals and general application of evidence based practice. When it comes to healthcare, challenges are constantly rising and therefore nurses should have adequate skills and well-developed reasoning skills as necessary for handling these tasks. Aim of work: Toexplore the evolution of nursing education, examining its historical development, the factors shaping its progress, and the strategies for preparing future generations of nurses for the complexities of modern healthcare. Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Evolution, Nursing Education, Preparing, Future Generations, Healthcare, and Challenges. The search was restricted to publications from 2016to 2024in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Several changes in the nursing education show the nursing profession’s obligation to adapt to the changing healthcare environment and train nurses for the future. Over the years, the nursing education has evolved from its humble beginnings in apprenticeship forms to more academic forms and preparedness, innovation as well as competencies needed in the diverse roles of a nurse. Due to the continuous advancement of healthcare, the educational process in nursing should not only adopt and incorporate new technologies, teaching practices, and ideas, but also should have a global focus. By doing so, it will guarantee that the future generations of the nurses are equipped with the knowledge to evidence-based practices and are capable of delivering a quality as well as compassionate care within the current and future health care settings.